PENDAMPINGAN LITERASI MAKANAN HALAL DAN THAYYIB BAGI GEN Z DI SMK AS-SHOLIHUDIN, KABUPATEN MALANG - Hakim, Rahmad; Hakim, Arif Luqman; Amalia, Rahmi; Millatina, Afifah Nur (Bulletin of Community Service and Development, 2025)
Purpose of the study: The purpose of this activity is to improve halal and good food literacy among Gen Z at As-Shallihudin Vocational School, Malang Regency. Methodology: Implementation methods that refer to the mutually agreed upon analysis of the program situation are discussions, outreach, interactive dialogues. Main Findings: Gen Z's halal and good food literacy is still low, and many are unaware of the urgency and benefits of halal and good food. Applications of this study: This community service is useful for Gen Z in improving halal and good food literacy. Novelty/Originality of this study: Improving halal and good food literacy among Gen Z.